Failure to Detect Hemagglutination-Inhibiting Antibodies with Intact Avian Influenza Virions - Lu, Bao-Lan (1982)
Avian influenza viruses replicate in a variety of mammals and birds, yet hemagglutination inhibition tests show that postinfection sera from these animals (e.g., ferrets and ducks) have insignificant levels of antibodies (Hinshaw et al., Infect. Immun. 34:354-361, 1981). This suggested that avian influenza viruses, in contrast to mammalian viruses, may not induce a significant humoral response. Studies reported here indicate that avian influenza viruses do induce high levels of antibodies in ferrets, ducks, and mice and produce long-lived memory for cytotoxic T-cells in mice. The failure to detect hemagglutination-inhibiting antibodies to avian viruses was explained by the finding that antibodies to avian influenza viruses were not detectable in hemagglutination inhibition tests with intact virus yet were readily demonstrable when hemagglutinin subunits were used. In addition, these sera contained high levels of neutralizing antibodies to the avian virus. These findings suggest that the hemagglutinins of avian and mammalian influenza viruses may differ in their accessibility to antibodies or the biological consequence of antibody attachment or both. The practical consequence of these studies is that hemagglutination inhibition tests with intact avian viruses fail to detect antibody and do not correlate with virus neutralization. The avian virus used in these studies, A/Mallard/NY/6870/78 (H2N2), replicated and caused mortality in BALB/c mice, emphasizing that the host range and virulence of avian viruses extends to mammals. The above findings suggest that avian viruses could infect mammals in nature, yet seroepidemiological studies with conventional hemagglutination inhibition tests could give misleading results.